WORKSHOP PENULISAN BUKU AJAR DAN ARTIKEL ILMIAH DI SMK NEGERI 5 SURABAYA - Heri Suryaman; Suparji; Soeparno; Gde Agus Yudha Prawira Adistana; Djoni Irianto; Hendra Wahyu Cahyaka (Universitas Negeri Surabaya, 2025)
One of the main problems with the implementation and teaching and learning process is the need for teachers for textbooks as teaching aids. This is because textbooks function as teaching aids to deliver lessons. With Permenpan and RB No. 16 concerning Teacher Functional Positions and Credit Points, the second problem regarding teacher scientific publications is further strengthened. Initially, teachers who were promoted from Group IV/a and above were only required to publish scientific publications, but now, with this Permenpan and RB, teachers who were promoted to Group III/c must do so. Then, in the analysis of the situation, several teachers at SMK Negeri 5 Surabaya still lacked knowledge and skills in making textbooks and scientific articles. The implementation methods used were socialization, training, practice, and sustainability of PKM activities. Therefore, the Unesa PKM team provided training to make textbooks and scientific articles through workshop activities on writing textbooks and scientific articles. The results of the PKM implementation showed that 86% of participants experienced an increase in knowledge regarding writing textbooks and scientific articles. This activity can improve the quality of writing skills for textbooks and scientific articles.